Peculiarities of inclusive resource centers implementation in Ukraine - Yevchenko, M.; Bielova, O.; Бєлова, Олена Ігорівна (Університет «КРОК», 2020)
Promoting equal access to quality education is an international agenda. In Ukraine, many changes have been made along the way, both at the level of legislation and at the level of practice: changes have been made to the basic Laws of Ukraine on the development and implementation of inclusive education; created conditions for teaching children and youth with special educational needs on the basis of many preschool, secondary and higher education institutions, training teachers to work in an inclusive educational environment, etc. At the same time, there are still many challengesalong the way: lack of resources, experience, understanding of the main advantages of this new philosophy of education. The modern paradigm of education is based on the idea of creating adequate conditions for individuals with different learning needs (including for people with various mental and physical disabilities and gifted people). Modern educational practices and pedagogical systems of developed and developing countries are undergoing the necessary changes in society, making the transition to new educational concepts and technologies. International organizations recommend inclusive education as a priority for the development of the education system, aimed at realizing the rights of citizens to receive quality education and social integration.The underpinning principal is that all children have the right to be educated regardless of their special needs, disabilities and abilities with appropriate support provided. In order to make the education system inclusive and provide education for all citizens, the Ministry of Education and Science of Ukraine together with other stakeholders developed strategies which support the education of children with special educational needs and initiated thecreation of the inclusive resource centers(IRC).The aim of this study is to highlight new approach on theoretical justifications and applied calculations necessary to ensure the implementation of inclusive resource centers.This article focuses on implementation of inclusive resource centers in Ukraine. The article also presents target audience, characterizes the profiles of children withspecial educational needs, their parents and teachers. Competitiveness of substituteinstitutions is analyzed using parametric method and the method with the weighted indicators. To evaluate the project alternatives, the «SPACE»method is applied. The article demonstrates the international experience oftwo modelsofіnclusive resource centers

Забезпечення рівноправного доступу до якісної освіти є міжнародною програмою. В Україні на цьому шляху здійснено чимало змін як нарівні законодавства, так і на рівні практики: внесені зміни в основні Закони України про розвиток і впровадження інклюзивної освіти; створені умови для навчання дітей і молоді з особливими освітніми потребами на базі багатьох дошкільних, загальноосвітніх і вищих навчальних закладів, здійснюється підготовка педагогів до роботи в умовах інклюзивного освітнього середовища тощо. Водночас ще й досі багато викликів постає на цьому шляху: це брак ресурсів, досвіду, розуміння основних переваг цієї нової філософії освіти. Сучасна парадигма освіти виходить з ідеї створення адекватних умов для індивідуумів з різними потребами в навчанні (в тому числі для осіб з різними психофізичними вадами та обдарованих людей). Сучасні освітні практики та педагогічні системи розвинених країн та країн що розвиваються зазнають необхідні соціуму зміни, здійснюючи перехід на нові освітні концепції та технології. Міжнародні організації в якості пріоритетного розвитку системи освіти рекомендують інклюзивну освіту, спрямовану на реалізацію прав громадян на здобуття якісної освіти та соціальну інтеграцію.Основним принципом є те, що всі діти мають право на освіту незалежно від особливих потреб, обмежених можливостей та здібностей за умови надання відповідної підтримки. Для того, щоб зробити систему освіти інклюзивною та забезпечити освіту для всіх громадян,Міністерство освіти і науки України спільно з іншими зацікавленими сторонами розробило стратегії, що підтримують навчання дітей з особливими освітніми потребами, та ініціювало створення інклюзивно-ресурсних центрів (ІРЦ). Метою цього дослідження є висвітлення нового підходу щодо теоретичних обґрунтувань та прикладних розрахунків, необхідних для забезпечення реалізації інклюзивних ресурсних центрів. Також стаття присвячена впровадженню інклюзивно-ресурсних центрів в Україні. У статті також представлена цільова аудиторія, охарактеризовані профілі дітей з особливими освітніми потребами, їх батьків та вчителів. Проаналізовано конкурентоспроможність закладів-субститутів за допомогою параметричного методу та методу з урахуванням зважених показників. Для оцінки альтернатив проекту застосовувся метод «SPACE». Стаття демонструє міжнародний досвід двох моделей інклюзивно-ресурсних центрів
Keywords: inclusive resource center; inclusiveresource center implementation; children with SEN; UN Convention on the rights of persons with disabilities; інклюзивно-ресурсний центр; впровадження інклюзивно-ресурсного центру; діти з ООП; Конвенція ООН про права інвалідів